Placenta Accreta: Obstetrician’s Nightmare; A Case Series of Seven Patients - Choudhary, Deepti; Nigam, A; Yadav, R; Choudhary, S; Raghunandan, C (Nepal Journal of Obstetrics and Gynaecology, 2013)
The incidence of placenta accreta is increasing as a consequence of rising number of cesarean sections and advancing maternal age. A series of seven cases of placenta accreta observed in a short span of four months is being presented. Complication rates in the present series are post partum hemorrhage and major transfusion support (100%), peripartum hysterectomy (100%), ICU admission in four (57%), fever (14%) and bladder injury in one case (14%). Nepal Journal of Obstetrics and Gynaecology / Vol 7 / No. 1 / Issue 13 / Jan- June, 2012 / 56-58 DOI: http://dx.doi.org/10.3126/njog.v7i1.8839